Hierarchical Optimization and Grid Scheduling Model for Energy Internet: A Genetic Algorithm-Based Layered Approach - Lin, Lihua; Abdallah, Abdallah; Ishak, Mohamad Khairi; Ali, Ziad M.; Khan, Imran; Rabie, Khaled; Safak Bayram, Islam; Li, Xingwang; Madsen, Dag Øivind; Kim, Ki-Il (Frontiers in Energy Research, 2022)
The old economic and social growth model, characterized by centralized fossil energy consumption, is progressively shifting, and the third industrial revolution, represented by the new energy and Internet technology is gaining traction. The energy Internet, as a core technology of the third industrial revolution, aims to combine the renewable energy and Internet technology to promote large-scale use and sharing of the distributed renewable energy, as well as the integration of multiple complex network systems such as electricity, transportation, and natural gas. Energy Internet is a new technology that enables the power networks to save energy. Multi-energy synchronization optimization, on the other hand, is a significant problem. This paper proposes an optimized approach based on the concept of layered control-collaborate optimization to solve this problem. The proposed method allows the distributed device to plan the heat, cold, gas, and electricity in the regional system in the most efficient way possible. The proposed optimization model is simulated using a real-number genetic algorithm. It improved the optimal scheduling between different regions and the independence of distributed equipment with minimal cost. Furthermore, the inverse system and energy and cost saving rate of the proposed method is better than existing methods which proved its effectiveness.